Diagnosis lies in the eyes of beholder: Linear gingival erythema in a non-HIV pediatric patient - Khushboo Gupta; Saurabh Singh; Sathya Kannan (Wolters Kluwer Medknow Publications, 2019)
Linear gingival erythema (LGE), formally referred to as HIV gingivitis, is the most common form of HIV associated periodontal disease in the HIV infected population. There is now evidence that this disease also occurs in HIV negative immunocompromised individuals and is not specific to HIV infection. A 13 years old boy presented with gingival inflammation in upper and lower anterior teeth mimicking LGE, but blood investigations showed HIV negative status. The microbial sample from the affected area confirmed candida infection and antifungal therapy with scaling helped to resolve the lesion. This case report emphasis that the clinician should obtain an in depth medical history to investigate such a condition. If there are signs and symptoms suggesting a systemic disease such as HIV, appropriate diagnostic testing such as blood testing or cytology must be considered. Patients with LGE should undergo laboratory testing to ensure that any underlying disorder is diagnosed and treated at the earliest possible time.